2015
DOI: 10.3996/112014-jfwm-085
|View full text |Cite
|
Sign up to set email alerts
|

Current Land Bird Distribution and Trends in Population Abundance Between 1982 and 2012 on Rota, Mariana Islands

Abstract: The western Pacific island of Rota is the fourth largest human-inhabited island in the Mariana archipelago and designated an Endemic Bird Area. Between 1982 and 2012, 12 point-transect distance-sampling surveys were conducted to assess bird population status. Surveys did not consistently sample the entire island; thus, we used a ratio estimator to estimate bird abundances in strata not sampled during every survey. Trends in population size were reliably estimated for 11 of 13 bird species, and 7 species declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 33 publications
2
19
2
Order By: Relevance
“…Thus, we suggest that the lack of a difference in HPIs between Guam and Rota is mostly an issue of low statistical power. Rota’s intermediate level of HPIs could also reflect the lower abundance of insectivorous birds on Rota compared to Saipan (Camp et al 2009 , 2015 ), which may contribute to reduced direct predation of HPIs by birds. This possibility is corroborated by the findings of Davis et al ( 2008 ), who showed in a similar island system with invasive ants and HPIs that Christmas Island white-eyes ( Zosterops natalis ) forage extensively on ant-tended scale insects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we suggest that the lack of a difference in HPIs between Guam and Rota is mostly an issue of low statistical power. Rota’s intermediate level of HPIs could also reflect the lower abundance of insectivorous birds on Rota compared to Saipan (Camp et al 2009 , 2015 ), which may contribute to reduced direct predation of HPIs by birds. This possibility is corroborated by the findings of Davis et al ( 2008 ), who showed in a similar island system with invasive ants and HPIs that Christmas Island white-eyes ( Zosterops natalis ) forage extensively on ant-tended scale insects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently estimated densities of Rufous fantails are slightly higher on Rota (651 ± 16 individuals/km 2 ) compared to Saipan (469 ± 63 individuals/km 2 ), although Saipan has much higher densities of bridled white-eyes ( Z. conspicillatus ) (4713 ± 387 individuals/km 2 ) and golden white-eyes ( C. marchei ) (711 ± 112 individuals/km 2 ) compared to densities of Rota white-eyes ( Z. rotensis ) (450 ± 14 individuals/km 2 ) (Camp et al 2009, 2015); Rota white-eyes have not been recorded at our study sites. Finally, Saipan also has insectivorous Mariana swiftlets that are locally extirpated from Rota.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2013 ). The potential impact of recent declines in some frugivorous bird species on Rota ( Camp et al . 2014 ) was not evident in our study, as a similar per cent of seeds in the seedbanks on Rota as on Saipan likely arrived through vertebrate dispersal (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the nearby islands of Saipan ( Camp et al . 2009 ) and Rota ( Camp et al . 2014 ), which both support similar limestone forest to Guam, have a more intact disperser assemblage, though some populations in Rota are declining ( Camp et al .…”
Section: Introductionmentioning
confidence: 99%